Scholarly Journal Publishing Forums in Tanzania Universities: An Insight - Samzugi, Athumani S.; Kagugu, Azizi H. (University of Dar es Salaam Library Journal, 2023)
The paper provides insights into scholarly journal publishing forums in Tanzania universities. It contextualises the current state of scholarly publishing and factors militating them in addition to providing possible palliatives for addressing them. The study employed a survey research design to collect both qualitative and quantitative data from websites, editors of journals, and directors of research at the universities under review. The results show that 63 (98.4%) of the scholarly journal forums are available at the selected universities. Journal editors indicated that 46 (71.9%) of their journals are both in print and electronic formats, followed by 11 (17.2%) who indicated only the electronic format as the mode of publication, whereas seven (10.9%) indicated only the print format. The results also show that 43 (67.2%) have adopted the open access philosophy, 16 (25%) have yet to do so and five (7.8%) remain non-committal. Considering the present journal publication realities, there is a need to review the publishing process to accommodate the online journal system (OJS) for the submission and processing of manuscripts. Furthermore, the study found the preferred mode to be a hybrid because the ICT infrastructure, cost of bandwidth, internet connectivity, and electricity remained an impediment to shifting to the purely online mode. Implicitly, academic journals for Tanzania ' s universities should currently be accessible in both print and electronic formats until when technologies dictate otherwise.